Psychological Stresses of Psychological and Educational Counselors in the Governorate of Ajloun in Jordan - Rami Tastoush; Ranya Mazahre (Sultan Qaboos University, 2010)
The study aimed to investigate the Psychological Stress of Psychological and Educational Counselors in public school in the Governorate of Ajloun in Jordan, and find out the effect of demographic variables of gender, qualification, experience in counseling, marital status and place of living on Psychological Stresses. The sample of the study comprised (61) male and female Counselors. The results revealed that the participants of the study showed a moderate degree of psychological stress. Work overload was the first reason of stress whereas job environment was the last reason. In addition, there were statistically significant differences in the degree of psychological stress due to qualification, experience, and marital status. There were no statistically significant differences in the degree of psychological stress due to gender and place of living.